The Effects of Self-esteem, Self-objectification, and Appearance Schemas on Clothing Choice Style: Examining the Structural Model - Zohre Alaedini; Sodabe Hasannejad (پژوهش‌های کاربردی روانشناختی, 2020)
The purpose of this study was to examine the structural model of the effects of self-esteem and appearance schemas on clothing choice style. The study was an applied and predictive research. The population included all students studying at Sepahanshahr universities in 2019-2020 academic year, from which 192 female students were selected using the convenient sampling method. The scales for assessment used in the study were Functions of Clothing (FC), Self-Esteem (SE), Appearance Schemas Inventory (ASI), Self-Objectification Beliefs, and Behaviors Scale (SOBBS), in addition to the demographic questionnaire. The results showed that self-esteem and appearance schemas affected clothing functions including “individuality”, “security”, and “mode” positively, and “camouflage” negatively. Self-esteem had the greatest impact on the function of "mode" and also predicted self-objectification ("body as self") negatively. Self-objectification ("the body as self") also indirectly (with the mediating role of the "self-evaluation schema") predicted all the functions of clothing (i.e., individuality, security, and mode) positively except for camouflage which was predicted negatively. Self-objectification ("body as self") and appearance schemas (self-evaluation) seem to play a mediating role in the relationship between self-esteem and functions of clothing. It is concluded that self-esteem and various aspects of body image (self-objectification and appearance schemas) influence the clothing choice style.